Surface Orientation of Magainin 2: Molecular Dynamics Simulation and Sum Frequency Generation Vibrational Spectroscopic Studies - Boughton, Andrew P. (2010)
We combined molecular dynamics based free energy calculations with Sum Frequency Generation (SFG) spectroscopy to study the orientational distribution of solvated peptides near hydrophobic surfaces. Using a simplified atomistic model of the polystyrene (PS) surface, molecular dynamics simulations have been applied to compute the orientational probability of an α-helical peptide, magainin 2, with respect to the PS/water interface. Free energy calculations revealed that the preferred (horizontal) peptide orientation was driven by the favorable interactions between the hydrophobic PS surface and hydrophobic residues on the helix, and additional simulations examined the importance of small aggregate formation. Concentration-dependent measurements obtained via SFG vibrational spectroscopy suggest that at very low peptide concentrations, magainin molecules tend to lie down at the PS/solution interface, which correlates well with the simulation results. When the concentration is increased, peptides exhibit behavior not captured by MD simulations using single helical peptides. A combination of simulations and experiments was shown to yield more reliable results with molecular-level insights into interaction between peptides and polymer surfaces.